On Ethical Responsiveness: Being Answerable to Others as an HCI Researcher. Issue 2 (27th January 2018) - Durrant, Abigail; Kirk, David
Abstract: In this paper we explore the practice of ethical responsiveness in Human–Computer Interaction (HCI) research, by presenting an empirical case study with a genocide memorial centre in Rwanda, focusing on researcher practice and experience. Our research investigated how this cultural institution operates, working with local and global communities and organizations to sustain its activities. We introduce our case to create a 'rich picture' of the ethical context for consideration. Drawing upon our autoethnographic insights as HCI researchers who were members of a larger project team, we will go on to provide a qualitative account of the ethical sensibilities that we engaged in the course of our case study, and specifically how, in conducting and reporting on the research, we chose to position ourselves relative to the institutional values of the centre and the personally held beliefs of its staff, as our research partners, participants, and stakeholders. We also address how our work dealt with broader ethical concerns of working in socially, culturally and politically sensitive settings. Our paper argument hinges around our developing practice of 'ethical responsiveness', grounded in established philosophies. We draw upon Pragmatist and Dialogical ethics to position researcher answerability within relationships between the key research partners and stakeholders. We further conceptualize ethics as a lived and emergent concern made manifest through these relationships, experienced in terms of feeling the ethical weight of being answerable to others and being responsive to this in terms of research process. We arrive at the following conclusion: to be answerable to others is to position yourself politically in relation to others. In closing we discuss the implications of this positioning for doing transnational and value sensitive design research in the HCI field.